Factors Influencing Student Satisfaction and Loyalty: A SEM-Based Study in Phnom Penh Universities - Chanbolin Heng; Sophearith Yeun; Ratha Sor (UTSAHA: Journal of Entrepreneurship, 2026)
Student satisfaction and loyalty are important indicators of institutional success in higher education. This study empirically validated a conceptual model of student satisfaction and loyalty in Phnom Penh universities, Cambodia. Building upon the structured literature review, the study identified five key determinants of student satisfaction, namely teaching quality, college administration, campus life and social integration, infrastructure facilities, and institution reputation. A quantitative research design was employed using online survey data collected from 450 of year 2 to year 4 students in two private universities in Phnom Penh. Structural Equation Modeling (SEM) using SPSS Amos 23 was applied to test the hypothesized relationships between constructs. The measurement model was assessed using reliability and validity tests, while the structural model was evaluated through path coefficients, t-statistics, and R2 analysis. The results indicated that teaching quality was the most significant factor affecting student satisfaction, followed by institution reputation, infrastructure facilities, and campus life and social integration, while college administration had a positive but an insignificant impact on student satisfaction. Moreover, student loyalty was significantly influenced by student satisfaction. This study contributes to theoretical framework regarding to student satisfaction and loyalty under the context of tertiary education in Cambodia. In practice, the findings can help university managers develop strategies for attracting and retaining students in the increasingly competitive higher education environment.